2018
DOI: 10.1111/oik.05885
|View full text |Cite
|
Sign up to set email alerts
|

Habitat choice stabilizes metapopulation dynamics by enabling ecological specialization

Abstract: Dispersal is a key trait responsible for the spread of individuals and genes among local populations, thereby generating eco‐evolutionary interactions. Especially in heterogeneous metapopulations, a tight coupling between dispersal, population dynamics and the evolution of local adaptation is expected. In this respect, dispersal should counteract ecological specialization by redistributing locally selected phenotypes (i.e. migration load). Habitat choice following an informed dispersal decision, however, can f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 70 publications
1
23
0
Order By: Relevance
“…Examples of matching habitat choice in natural populations are still very scarce, though half of the field studies conducted to date have found inconsistencies in the relationship between the spatial distribution of phenotypes and the predicted optimal distribution. These inconsistencies are usually attributed to constraints on the expression of matching habitat choice, such as the exclusion from preferred habitats by dominant conspecifics (Camacho et al , Jacobson et al ) or the lack of alternative habitats (Edelaar et al , Mortier et al ). However, to our knowledge, the potential role of group‐specific costs of mischoosing as a constraint on the expression (and detection) of matching habitat choice has not been previously considered in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Examples of matching habitat choice in natural populations are still very scarce, though half of the field studies conducted to date have found inconsistencies in the relationship between the spatial distribution of phenotypes and the predicted optimal distribution. These inconsistencies are usually attributed to constraints on the expression of matching habitat choice, such as the exclusion from preferred habitats by dominant conspecifics (Camacho et al , Jacobson et al ) or the lack of alternative habitats (Edelaar et al , Mortier et al ). However, to our knowledge, the potential role of group‐specific costs of mischoosing as a constraint on the expression (and detection) of matching habitat choice has not been previously considered in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Matching habitat choice can have important evolutionary implications, as it may influence the degree and rate of local adaptation, determine individual performance, facilitate the maintenance of genetic variation and population persistence, and even lead to speciation (Edelaar et al , Berner and Thibert‐Plante 2015). Nevertheless, matching habitat choice has only recently received much attention, with the available evidence mostly coming from individual‐based simulations (Bolnick and Otto , Nicolaus and Edelaar , Mortier et al , Pellerin et al ) or laboratory organisms in experimental microcosms (Karpestam et al , Wennersten et al , Jacob et al , , Jacobson et al ). By contrast, field tests for natural populations are limited to a handful of studies, mostly on birds (Dreiss et al , Camacho et al , Benkman , Holtmann et al , but see Bolnick et al 2009, Edelaar et al , Lowe and Addis ), with their infrequency due in part to logistical and inferential challenges.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Feedbacks between movement as both an energy-consuming and an energy-gaining process are thus likely key to spatial behaviours in the wild, but to date poorly understood despite the increase of biologging studies across a wide variety of taxa [83]. Moreover, most insights on such conditional-dependent strategies come from studies that focussed on the active departure phases and neglected decision making in terms of settlement [84]. Given the link between body-condition and competitive ability, it remains to be studied to which degree presumed maladaptive departure decisions may eventually be compensated by facilitated settlement in new environmentsespecially when demographic and environmental conditions are strongly different between locations.…”
Section: A Threshold-view On Movement Decision Makingmentioning
confidence: 99%
“…Models vary how matching habitat choice is implemented. A simple possibility is that each individual chooses, from a certain number of patches, the patch where the locally optimal phenotype is closest to its own (Edelaar et al 2017;Mortier et al 2019); but this choice can be suboptimal due to crowding if many individuals choose the same patch. In other simulation models, the probability of dispersal is a prescribed function of the difference between the departure and target patches, with only its parameters evolving (Armsworth and Roughgarden 2005;Enfjäll and Leimar 2009; Berner and Thibert-Plante 2015); this function however ought to evolve freely.…”
Section: Introductionmentioning
confidence: 99%